Period prevalence of hypertension and risk factors in an urban slum of Maharashtra - Niwal, Ajinkya J. J.; Tambe, Muralidhar P.; Rao, S. P.; Parande, Malangori A. (International Journal Of Community Medicine And Public Health, 2019)
Background: One in three adults worldwide has high blood pressure and proportion increases with age. Detecting high blood pressure is easy. Hence a study for prevalence of hypertension was conducted in an urban slum of Pune, Maharashtra. Methods: The study was conducted in an urban slum field practice area exclusively under the community medicine department of a tertiary care hospital during the period of February 2014- July 2014. Overall 1043 people fulfilling the inclusion and exclusion criteria were interviewed, and anthropometric measurements were taken, followed by blood pressure readings and awareness of own hypertensive status. Data was compiled, edited, classified, and analyzed. The prevalence of hypertensive patients was obtained and physical and behavioral risk factors were analyzed for association. Results: The prevalence of hypertension in adults above 18 years of age was 25.6% with mean age of hypertensive patients was 48.58±15.75 yrs. Hypertension was significantly associated with age, habit of adding extra salt to cooked food, family history, BMI and consumption of smokeless form of tobacco among the study participants. Hypertension was not significantly associated with gender and religion of the participants. Of the 267 hypertensives, 40.82% were aware of their hypertensive status and amongst those aware 61.46% were on anti-hypertensives. Conclusions: Hypertension is a public health problem affecting slum population as well. It is significantly associated with risk factors, which are modifiable. The awareness of hypertensive status is low, the under treatment is lower. The population in slum, with its poor literacy, low awareness and income levels provides an opportunity to make an intervention necessary as well as challenging.